Correspondence of Emperor Alexander I and professor G. F. Parrot (1802–1825) as a source for the study of political reforms in Russian Empire - Andrei Andreev (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This article studies a unique historical source, i.e. the correspondence which for a number of years was kept up between Russian Emperor Alexander I and professor of the University of Dorpat Georg Friedrich Parrot. Their acquaintance in 1802 took place in the period when numerous liberal reforms in Russia were prepared, constitutional projects were discussed, and serfdom was abolished. Parrot also played a rather signifi cant role in the development of public education, in the opening of new schools in the Baltic provinces, and in the improvement of his own university. His impact on government policy was made possible by a special nature of the relationship, the “sincere friendship” that he established with Alexander I, as it was refl ected in their correspondence. The later fate of these letters after Parrot’s death came to be very complicated, and their scientifi c study has not been carried out until now. Much of the work that allowed historians to make themselves familiar with the content of the letters was done more than a hundred years ago, but since then specialists have not used the original source. Its detailed publication should be an immediate task due to the great informative potential contained in the letters and touching upon the key problems of the political development of the Russian Empire.